El Ars dictaminis, Cicerón y Quintiliano en el apócrifo De conficiendis epistolis (c. 1444-1447) de los Opera omnia de Lorenzo Valla - Bonmatí Sánchez, Virginia (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
The object of this essay is the methodological innovation carried out by an apocryphal humanist in treaty on epistolary style entitled De conficiendis epistolis (c. 1444-1447), attributed to Lorenzo Valla, comparing it with the medieval treaties on Ars dictaminis, after the discovery of Cicero’s and Quintilian’s works by Poggio Bracciolini in 1416 and by Gerardo Landriani in 1421, besides the influence of Gasparino Barzizza’s treaty De compositione (1420).